Environmental Credit Risk Assessment Lending Decisions and Bank Liabilities - Amourdon, Rosy anne (Université d'Ottawa | University of Ottawa, 2007)
Under the lender liability legislative framework, banks can be held liable for clean up costs caused by their corporate borrowers, in order to ensure proper internalization of an externality such as an environmental accident. The role that bank can play i